ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR PETANI - HENDAYANA, RACHMAT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 2, No. 2 Juli 2002)
his paper aim to identification and the affecting factors analysis of farmer’s exchange rate (FER). The survey was conducted in North Sumatera covers 60 farmers and 15 trader’s respondent in FY 1995/1996 using descriptive analysis with simple statistical model. The results indicated (a) During FY 1987-1994 periods, the trend of FER value was decreasing, (b) The value of FER affected by rice yield, output price, consumer goods price and the fertilizer price. The rice yield and output price are positive impact, while the fertilizer price is negative impact. (c) Through the regression models knowing that one percent FER improvement will be rising about 0.02 percent rice production and farmers income Rp 1.285,8. (d) To improvement of FER, the regulation or policy for out put and input price are needed. Keywords: Farmers exchange rate, rice yield, output, consumer goods, fertilizer and Farmer’s income.
Keywords: Farmers exchange rate, rice yield, output, consumer goods, fertilizer and Farmer’s income.